(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
hysical education and sports are of great importance in the formation of a healthy lifestyle, spiritual and physical development of student youth. Physical exercises strengthen health, increase neuropsychological activity to emotional stress, support physical and mental capacity. In recent years, certain works have appeared related to the study of health problems and a healthy lifestyle within the educational process of a professional school: general health issues of student youth are discussed; the spread of alcoholism and drug addiction in the youth environment is being analyzed; the influence of various factors on the formation of a healthy lifestyle of students is investigated; the nature and level of valeological knowledge of students is studied; conditions and means of forming a healthy lifestyle of young people are being searched for. Student age is characterized by intensive work on the formation of one’s personality, studying the style of behavior. Young people in this period have enormous opportunities for education and social activities. Therefore, physical culture and sports become really the most important means of strengthening health, a natural biological basis for personality formation, effective learning, and successful social activities. The formation of health can successfully take place in the conditions of the organization of a healthy lifestyle. Useful habits help in the formation of harmonious development of the personality, harmful - on the contrary, inhibit its formation. Habits are very stable. A healthy lifestyle cannot be acquired once and for all at some stage of education and personal development, as is the case with learning the multiplication table. A lifestyle can be healthy only when it develops, is supplemented with various new elements useful for health, habits and thereby improves. Therefore, a healthy lifestyle must be constantly learned, which means that he must constantly be taught, nurture the need for a healthy lifestyle. This concept includes physical culture as a constituent part.